IL-1 Inhibition May Have an Important Role in Treating Refractory Kawasaki Disease - Dusser, Perrine; Koné-Paut, Isabelle (Frontiers in Pharmacology, 2017)
Kawasaki disease (KD) is an acute inflammatory vasculitis occurring in young children before 5 years and representing at this age, the main cause of acquired heart disease. A single infusion of 2g/kg of intravenous immunoglobulins along with aspirin has reduced the frequency of coronary artery aneurysms from 25% to 5%. However, 10 to 20% of patients do not respond to standard treatment and have an increased risk of cardiac complications and death. The development of more potent therapeutic approaches of KD is an urgent need. Phenotypical and immunological similarities between KD and systemic juvenile idiopathic arthritis led to the hypothesis that KD could be considered as an autoinflammatory disease. New insights regarding KD’s pathogenesis have merged from the combination of genetic and transcriptomic data revealing the key role of interleukin-1 (IL-1) signaling in the pathogenesis of the vasculitis. Once activated, IL-1α and IL-1β trigger a local proinflammatory environment inducing vasodilatation and attracting monocytes and neutrophils to sites causing tissue damage and stress. Both IL-1α and IL-1β have been shown to induce myocarditis and aneurysm formation in LCCWE mouse model of KD; both being successfully improved with IL-1 blockade treatment such as anakinra. Treatment failure in patients with the high-risk ITPKC genotype was associated with highest basal and stimulated intracellular calcium levels, increased cellular production of IL-1β and IL-18, and higher circulating levels of both cytokines. Three clinical trials of IL-1 blockade enrolling KD patients are currently being conducted in Western Europe and in the U.S.A, they could change KD outcome.